2017
DOI: 10.1101/115709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiota analysis in rats with methamphetamine-induced conditioned place preference

Abstract: Methamphetamine abuse is a major public health crisis. Because accumulating evidence supports the hypothesis that the gut microbiota plays an important role in central nervous system (CNS) function, and research on the roles of the microbiome in CNS disorders holds conceivable promise for developing novel therapeutic avenues for treating CNS disorders, we sought to determine whether administration of methamphetamine leads to alterations in the intestinal microbiota. In this study, the gut microbiota profiles o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Odoribacter, Oscillospira and Anaerostipes also belong to the same taxonomic families. It was suggested that these gut microbiota are likely related to dopamine activity (40), as two studies in patients with Parkinson's disease (41,42) and another using a dopamine agonist in rats (43) revealed alterations of OTUs in the same family. Similarly, Quagliariello et al (2018) (8) reported that levels of Bacteroides , Odoribacter and Oscillospira were higher in the younger (ages 4–8 years vs. age 9) PANS group than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Odoribacter, Oscillospira and Anaerostipes also belong to the same taxonomic families. It was suggested that these gut microbiota are likely related to dopamine activity (40), as two studies in patients with Parkinson's disease (41,42) and another using a dopamine agonist in rats (43) revealed alterations of OTUs in the same family. Similarly, Quagliariello et al (2018) (8) reported that levels of Bacteroides , Odoribacter and Oscillospira were higher in the younger (ages 4–8 years vs. age 9) PANS group than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been demonstrated that similar bacterial species are affected by different and chemically diverse antipsychotics (Maier et al, 2018). Chronic alcohol abuse also alters gut microbiome composition (Leclercq et al, 2017), and other drugs of abuse possibly do the same, such as methamphetamine (Ning et al, 2017). More generally, substance use disorders are associated with reduced microbiota diversity (Xu et al, 2017).…”
Section: B Impact Of Current and Putative Therapeutic Interventions mentioning
confidence: 99%
“…The reciprocal communication between the gut microbiome and the CNS is referred to as the gutbrain axis [24]. With regard to drugs of abuse, a small but growing literature is establishing roles for the gut microbiome in alcohol abuse and withdrawal [25,26], opioid tolerance [27,28], nicotine and smoking [29], cocaine reward [30], and in Meth-induced conditioned place preference [31]. Finally, it has been shown that patients with substance use disorders (SUDs) show changes in gut bacterial diversity [32].…”
Section: Introductionmentioning
confidence: 99%